2019
DOI: 10.4014/jmb.1904.04028
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genomics Approaches to Understanding Virulence and Antimicrobial Resistance of Salmonella Typhimurium ST1539 Isolated from a Poultry Slaughterhouse in Korea

Abstract: Non-typhoidal Salmonella (NTS) is one of the most frequent causes of bacterial foodborne illnesses. Considering that the main reservoir of NTS is the intestinal tract of livestock, foods of animal origin are regarded as the main vehicles of Salmonella infection. In particular, poultry colonized with Salmonella Typhimurium (S. Typhimurium), a dominant serotype responsible for human infections, do not exhibit overt signs and symptoms, thereby posing a potential health risk to humans. In this study, comparative g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Fanelli et al identified a large number of antibiotic, heavy metals and virulence determinants by reporting the whole genome sequencing and genomic characterization of two Arcobacter butzleri strains isolated from shellfish [ 14 ]. Similarly, the virulence and antimicrobial resistance-associated genomic determinants of two Salmonella Typhimurium strains were reported through comparative genomics approaches [ 15 ]. Although some complete genome sequences of S.iniae isolated have been sequenced, to our knowledge, there have been no reports on the comparative genomics analysis for understanding the genetic basis of pathogenicity and multidrug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Fanelli et al identified a large number of antibiotic, heavy metals and virulence determinants by reporting the whole genome sequencing and genomic characterization of two Arcobacter butzleri strains isolated from shellfish [ 14 ]. Similarly, the virulence and antimicrobial resistance-associated genomic determinants of two Salmonella Typhimurium strains were reported through comparative genomics approaches [ 15 ]. Although some complete genome sequences of S.iniae isolated have been sequenced, to our knowledge, there have been no reports on the comparative genomics analysis for understanding the genetic basis of pathogenicity and multidrug resistance.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalent Salmonella is widely found in diverse sources, including environment, animal-originated foods, water, and animals, specifically wild animals, including wild birds [ 11 , 12 , 13 ], wild pigs [ 14 ], poultry and their eggs [ 15 ], and cattle [ 16 ]. It can be disseminated to humans via ingestion of contaminated food of animal origins, including pork, chicken, eggs, beef, and milk [ 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%